THE ROLE OF JOB SATISFACTION IN MEDIATING THE RELATIONSHIP BETWEEN WORK ENVIRONMENT AND LEADERSHIP STYLE ON TEACHER PERFORMANCE AT STATE SENIOR HIGH SCHOOL - Diana Sarah; Ine Rahayu Purnamaningsih; Saepul Ma'mun (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aims to deeply understand the role of job satisfaction as a mediator in the relationship between the work environment and leadership style on teacher performance. A qualitative approach was used to uncover the experiences, perceptions, and dynamics experienced by teachers in the context of the work environment and leadership style applied in schools. The results of the study indicate that job satisfaction plays an important role in strengthening the positive influence of the work environment and leadership style on teacher performance. Teachers who feel satisfied with their work tend to be more motivated and perform optimally, especially when supported by a conducive work environment and an inspirational leadership style. These findings emphasize the importance of paying attention to psychological and social aspects in improving teacher performance through appropriate management of the work environment and leadership style. This study contributes to the development of educational management theory and leadership practice in school environments.